Analysis of Adaptive Reuse Building for Early Childhood School: Optimizing Interior Design for Child Development - Tanzillah, Nury; Sakya, Kharista Astrini (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The conversion of unused or abandoned buildings into educational facilities, known as adaptive reuse, is a common practice in school construction. The process involves transforming old buildings to meet new educational needs. While adaptive reuse is considered an innovative and sustainable solution, research shows that this approach often does not support optimal child development. This research explores the application of educational principles in the context of adaptive reuse with a focus on creating learning spaces suitable for early childhood education. The method used involved a qualitative approach with an open-ended questionnaire administered to school principals, teachers, staff and parents. The questionnaire was designed to elicit understanding and perceptions of how interior design can support children's physical, emotional and social development. The novelty of this study lies in the integration of interior design principles specific to early childhood education in the context of adaptive reuse. Different from previous studies that focus on structural or functional aspects, this research offers practical guidance to transform old buildings into learning spaces that support various aspects of children's growth. The results reveal that adaptive reuse applications often do not fulfill all important aspects of designing learning environments. Key issues identified include limitations in creating spaces that support children's creativity, safety, comfort and social interaction. This research emphasizes the need for a more integrated and developmentally-focused design approach to ensure that the resulting learning spaces truly support various aspects of children's growth and learning.